Behaviour of carbon nanotubes-Cr2O3 thermal barrier coatings in actual boiler. (1st February 2020) - Goyal, Khushdeep; Singh, Hazoor; Bhatia, Rakesh
ABSTRACT: Hot corrosion behaviour of Carbon Nanotubes (CNT) reinforced Cr2 O3 composite coatings have been investigated in actual boiler environment of a thermal power plant at 900°C under cyclic thermal loading conditions. The CNT content was varied from 1 to 8 wt-% and the coatings were deposited with the high-velocity oxy-fuel method. The comparative effects of variation in CNT content (from 1 to 8 wt-%) on hot corrosion behaviour were studied by weight change analysis and corrosion products were analysed with X-ray diffraction, scanning electron microscopy, energy dispersive and cross-sectional analysis techniques. The results confirmed that variation in CNT content enhanced the corrosion resistance of surface coatings in actual boiler environment at elevated temperature. The coatings showed lower weight gain along with the formation of protective oxide scales during the experiment. Reduction in corrosion rates during hot corrosion was observed with an increase in CNT content in the coating matrix.